Adult-onset hypoxaemia, diffuse lung lesions, and pulmonary hypertension in cobalamin C defect: a case report. Issue 6 (30th June 2021) - Zhao, Qin-Hua; Wu, Wen-Hui; Fu, Li-Jun; Wang, Lan
Abstract: Background: Cobalamin C (cbl-C) defect is an inherited autosomal recessive disorder that commonly affects the central nervous system of infants. Severe pulmonary hypertension (PH) and diffuse lung lesions are unusual clinical manifestations, especially among adults. Case summary: A 25-year-old man with hypoxaemia, diffuse lung lesions, and PH, suddenly developed nausea, vomiting, headache, and worsening of dyspnoea. Metabolic screening showed elevated serum levels of methylmalonic acid and homocysteine, and genetic testing revealed MMACHC gene mutations. He was eventually diagnosed with severe PH secondary to cbl-C defect and was successfully managed with vitamin B12, betaine, L-carnitine, folate, as well as ambrisentan and sildenafil. Discussion: cbl-C is a rare cause of PH and can present with severe PH and diffuse lung lesions in adults. Given that the condition is treatable, a careful metabolic screening should be considered when a diagnosis of PH is made.